4, 5, 6, 7-Tetrabromo-2, 3-dihydro-1, 1, 3-trimethyl-3-(2, 3, 4, 5-tetrabromophenyl)-1H-indene (OBTMPI): Levels in humans and in silico toxicological profiles. (15th March 2021) - Das, Dharani; Kulkarni, Sunil; Barton-Maclaren, Tara; Zhu, Jiping
Abstract: Limited human exposure and toxicity data are currently available for 4, 5, 6, 7-Tetrabromo-2, 3-dihydro-1, 1, 3-trimethyl-3-(2, 3, 4, 5-tetrabromophenyl)-1H-indene (OBTMPI), a flame retardant often used for high temperature application of various polymer materials. Levels of OBTMPI in a cohort population that includes children and their co-residing parents (n = 217) in Canada were determined. Detection frequency of OBTMPI in the samples was 22.6%. OBTMPI levels were in general at sub-to low ng/g lipid weight level with a 95th percentile at 15.6 ng/g lipid weight. Compared to an earlier study conducted in 2008–2009 in the same region, results from this study show an increase in both detection frequency and concentration of OBTMPI. In silico toxicity predictions using Multicase CaseUltra and Leadscope Model Applier suggested that OBTMPI, and its possible metabolites in humans, while unlikely to be carcinogenic or mutagenic, exhibit some estrogen antagonist, androgen antagonist and estrogen binding capability reflective of possible endocrine disrupting properties. Graphical abstract: Image 1 Highlights: Possible rise in levels of emerging flame retardant OBTMPI in humans in Canada. Exposure to OBTMPI among child, mother and father living in the same household. In silico prediction of endocrine disruption properties for OBTMPI and metabolites. Abstract : Emerging flame retardant OBTMPI is present in humans and endocrine disruption predicted by in silico is a likely adverse effect of OBTMPI.